504PA single center report for safety and efficacy of CT-707 in Chinese patients with advanced, anaplastic lymphoma kinase-rearranged non-small cell lung cancer or other tumours. (24th November 2019) - Song, P; Zhang, L
Abstract: Background: It is proved that anaplastic lymphoma kinase-rearranged non–small-cell lung cancer (ALK-rearranged NSCLC) is sensitive to ALK inhibitors while the chemotherapy resistance is unavoidable. In this study, safety and antitumor activity of the novel ALK inhibitor (ALKi) CT-707 is evaluated in Chinese patients with advanced ALK-rearranged NSCLC. Methods: This Multi-center, open-label phase I study (NCT02695550) recruited adult patients with ALK-rearrangement (confirmed by fluorescence in situ hybridization and/or immunohistochemistry) of locally advanced/metastatic malignancies including non–small-cell lung cancer. This study consisted of a dose escalation study and a dose expansion study. CT-707 was administered orally once a day for 21 days. The Lung Cancer Center of Peking Union Medical College Hospital of Chinese Academy of Medical Sciences summarized the safety and effectiveness of the cases enrolled in this center. Results: Thirteen patients who were treated with CT-707 from 450 to 600mg (in the dose increasing phase) were enrolled in this trial (two patients were previously treated with crizotinib). Twelve patients were diagnosed with lung adenocarcinoma and one patient was malignant pleural mesothelioma. After treatment, grade 3 diarrhea (600 mg QD) was found as dose-limiting toxicity (DLT). The most common adverse events included diarrhea (92%), elevated aspartate aminotransferase (61%), elevated alanine aminotransferase (54%), hair loss (38%), and vomiting (31%).ORR and disease control rate among patients were 10 of 13 (77%) and 11 of 13 (85%). The median progression-free survival was 13 months (95% CI:9.98-16.00).The overall survival rate of 12 months was 85%, which has not yet reached the median overall survival. Among all patients, ten patients observed partial response (PR). One patient reached a complete response (CR). However, no response of the disease was observed in patients with malignant pleural mesothelioma. Conclusions: CT-707 is effective in Chinese patients with tumors harboring ALK rearrangements. It has reliable safety and tremendous clinical application value. Clinical trial identification: NCT02695550; March 2016. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.